TINJAUAN SISTEMATIK: KECEMASAN PASIEN PENYAKIT GINJAL KRONIK DENGAN TINDAKAN HEMODIALISIS - Santoso, May Dwi Yuri (Jurnal Kesehatan Mesencephalon, 2018)
The action of hemodialysis in patients with chronic kidney disease can trigger anxiety due to situational crisis, death threat and not know the final result of hemodialysis action. The purpose of this systematic review is to gain an understanding of the anxiety of patients with chronic kidney disease with hemodialysis action. The results of a review of 15 journals that have been selected suggest that patients with chronic kidney disease with hemodialysis actions mostly experience anxiety. The most widely used instruments are (HADS) Hospital Anxiety And Depression Scale (n = 5). Factors affecting anxiety of chronic kidney disease patients with hemodialysis action are social demographic factors such as sex, age, occupation, duration of hemodialysis and education. Other factors are psychological, social perception, non pharmacological action (progressive muscular), (aroma therapy) and spiritual intelligence. The conclusion that anxiety disorder is very important, and appropriate Instrument will affect patient objective anxiety results. The need for a team collaborative approach to reduce anxiety of patients with chronic kidney disease by hemodialysis.Â Keywords : Anxiety, Chronic Kidney Disease, Hemodialysis